Dulaglutide 1.5 mg as an add‐on option for patients uncontrolled on insulin: Subgroup analysis by age, duration of diabetes and baseline glycated haemoglobin concentration. Issue 6 (23rd March 2018) - Pantalone, Kevin M.; Patel, Hiren; Yu, Maria; Fernández Landó, Laura
Abstract : Aims: To assess efficacy and safety of dulaglutide 1.5 mg combined with insulin, categorized by subgroups of baseline glycated haemoglobin (HbA1c; ≤9% and >9% [≤74.9 and >74.9 mmol/mol]), age (<65 and ≥65 years), and duration of diabetes (<10 and ≥10 years) at 6 months in patients with type 2 diabetes (T2D). Materials and methods: This pooled analysis was conducted in a population of patients with T2D with similar baseline characteristics who were included in the AWARD‐4 and AWARD‐9 clinical trials and randomized to dulaglutide 1.5 mg (pooled mean baseline age 59 years, duration of diabetes 13 years, HbA1c 8.4% [68.3 mmol/mol]). Weight and hypoglycaemia were analysed by individual trial. In AWARD‐4, dulaglutide plus lispro three times daily was assessed against glargine plus lispro three times daily. In AWARD‐9, dulaglutide added to glargine was assessed against placebo added to glargine. Insulins were titrated to target in both trials. Results: A total of 445 patients were included in this analysis (73% with HbA1c ≤9%, 27% [≤74.9 mmol/mol] with HbA1c >9% [>74.9 mmol/mol]; 70% aged <65 years, 30% aged ≥65 years; 36% with duration of diabetes <10 years, 64% with duration of diabetes ≥10 years). At 6 months, dulaglutide 1.5 mg significantly reduced HbA1c in all subgroups ( P  < .001), with the highest reduction observed in patients with baseline HbA1c >9% (>74.9 mmol/mol) (range − 1.3% to −2.5% [−14.2 to −27.3 mmol/mol]). The incidence rates of documented symptomatic and severe hypoglycaemia were similar in all subgroups in both trials. The most common adverse events observed in each trial were gastrointestinal in nature. Conclusion: Dulaglutide 1.5 mg combined with basal or prandial insulin is efficacious for patients with T2D irrespective of age, duration of diabetes or baseline HbA1c.